Telecommunication operator’s transition to the omnichannel architecture - Леонід Смідович; Юрій Кулик; Мирослав Момот (Сучасний стан наукових досліджень та технологій в промисловості, 2024)
The subject matter of the article is the omnichannel architecture of information systems of telecom operators, functional requirements for it and the processes of transformation from multichannel to omnichannel architecture. The goal is to elaborate the reference architecture of telecommunication operator’s omnichannel platform, and to transform the existing information architecture according to the principles of omnichannel approach and open digital architecture, what will improve customer experience, increase telecommunication operator’s competitiveness and customer loyalty. The following tasks were solved at the study: analysis of the current state of information systems in telecommunications; analysis of marketing and technical drivers for transition from multichannel to omnichannel architecture, analysis of specifics of omnichannel approach implementation in telecommunications and related challenges, analysis of functional and system requirements for telecommunication operator’s omnichannel platform, elaboration of the reference omnichannel architecture, elaboration of a recommendations for the process of transformation from the existing multichannel architecture of the communication operator to the target omnichannel architecture. To solve these problems, methods of system and business analysis were used, in particular, methods of analysis of software requirements, technologies for developing software application architecture. The following results were obtained. The current state of the telecommunications services industry in part of customer engagement, and related approaches ‒ the multichannel and the omnichannel one ‒ were analysed. The functional and non-functional requirements to omnichannel implementation were considered. Reference functional and component architecture of omnichannel customer engagement function was proposed. Strategies of transition to modern omnichannel architecture were considered and analysed. Conclusions: implementation of omnichannel approach in telecommunications and transition to omnichannel architecture require transformation of CSP’s informational architecture itself. It should be performed according to principles of Open Digital Architecture (ODA), and developed in frames functional blocks of ODA. Such a transformation will ensure improving of customer experience, increasing customer satisfaction and customer loyalty, allow CSPs to increase competitiveness by reduce operating costs, improving operational efficiency, and overall business performance.